How can we solve the social crisis after COVID-19 and before robotization of workplace in the EU and national level – basic income or general minimum wage? - Mélypataki, Gábor (Z Problematyki Prawa Pracy i Polityki Socjalnej, 2022)
The changes of the labour market have strong characteristics compared to the earlier eras. These changes are primarily the changes happening due to the process of digitalization coming to the foreground which will significantly transform the structure of the labour market2. The time shift between the terminating workplaces and the new ones resulting from the application of new technologies and the retraining of the employees will result in an intermediate time interval. The maximal use of this time interval will be typical mainly for the low-educated manpower. However, based on the principle of national social care, these people cannot be left without provision. This problem has become really urgent because of the COVID-19 epidemic reaching Europe on the spring of 2020. More countries have introduced basic income or a similar kind of social benefit. The reason for this step is the significant employment crisis which is the consequence of the lock-down that has been applied in certain countries in order to stop the spread of the virus. But basic income is only one element of the system, so the issue should be examined in terms of minimum wage and minimum income.